THE INFLUENCE OF SUPPLY CHAIN MANAGEMENT ON COMPANY PERFORMANCE THROUGH COMPETITIVE ADVANTAGE AS AN INTERVENING VARIABLE (Study at PT Berlian Gresik - INDONESIAN) - Hafi, Mohammad (Program Doktor Ilmu Ekonomi, 2021)
Given the Covid-19 pandemic, most companies are currently facingsupply chain risks in the future. This provides a common thread thatmaintaining the stability of industrial supply chain management duringthe Covid-19 pandemic is a very important matter, including for PTBerlian Gresik. Based on the objectives, this study used a designexplanatory research (hypothesis testing) with the causality approachwhich aims to explain causal relationships. The population in this studyconsisted of all employees at PT Berlian Gresik, totaling 96 employees.While the sampling technique in this study used a saturated samplingmethod, so that the sample used was also a number of existingpopulations. The analysis technique used is structural equationmodeling with the Smart PLS 3 program tools. The results of this studyare (1) Supply Chain Management positive and significant effect onCompany Performance; (2) Supplay Chain Management positive andsignificant effect on Competitive Advantage; and (3) CompetitiveAdvantage has a positive and significant effect to CompanyPerformance.